Development of Problem-Based Learning-Based Teaching Module on Number Pattern Content to Facilitate Mathematical Problem-SolvingAbility of Grade VII Students - Putri Yuanita; Sudiro, Yolanda Tesalonika; Sakur (UNNES JOURNAL, 2025)
The Merdeka Curriculum emphasize the importance of mathematical problem-solving ability (MPSA) to face the challenges of learning and everyday life. Previous studies have largely focused on learning models without developing contextual and specific teaching materials. This study aims to develop a teaching module based on Problem-based Learning (PBL) for number pattern content to enhance the MPSA of phase D students. The research employed the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Research instruments included validation sheets and practicality questionnaires. The validation results indicated a very valid category with an average score of 3.65, while the LKPD practicality reached a very practical category with an average score of 3.35. Based on the research results, it can be concluded that the problem-based learning-based teaching module can facilitate the mathematical problem-solving skills of seventh-grade students. This research also shows a significant increase in the students' MPSA after the implementation of the PBL Teaching Module, marked by an increase in the average score from pre-test to post-test, and students also demonstrated a more positive attitude and higher self-confidence towards mathematics. The development of the PBL-based teaching module not only enhances the quality of mathematics learning but also helps students develop the Pancasila learner profile. Abstrak Kurikulum Merdeka menekankan pentingnya kemampuan pemecahan masalah matematis (KPPM) untuk menghadapi tantangan belajar dan kehidupan sehari-hari. Penelitian sebelumnya lebih banyak menyoroti model pembelajaran tanpa mengembangkan perangkat ajar yang kontekstual dan spesifik. Penelitian ini bertujuan mengembangkan modul ajar berbasis Problem-Based Learning (PBL) untuk konten pola bilangan guna meningkatkan KPMM peserta didik kelas VII. Penelitian menggunakan model pengembangan ADDIE (Analysis, Design, Development, Implementation, Evaluation). Instrumen penelitian berupa lembar validasi dan lembar praktikalitas. Hasil validasi modul menunjukkan kategori sangat valid dengan rata-rata skor 3,65, sedangkan praktikalitas LKPD mencapai kategori sangat praktis dengan rata-rata skor 3,35. Berdasarkan hasil penelitian dapat disimpulkan bahwa modul ajar berbasis problem-based learning dapat memfasilitasi kemampuan pemecahan masalah matematis peserta didik kelas VII. Penelitian ini juga menunjukkan adanya peningkatan yang signifikan dalam KPMM peserta didik setelah penerapan Modul Ajar PBL, ditandai dengan peningkatan rata-rata skor dari pre-test ke posttest, serta peserta didik juga menunjukkan sikap positif dan kepercayaan diri yang lebih tinggi terhadap matematika. Pengembangan modul ajar berbasis PBL tidak hanya meningkatkan kualitas pembelajaran matematika, tetapi juga membantu peserta didik mengembangkan profil pelajar Pancasila.